Impact of chemical and microbiological water quality on bacterial community assemblage of San Juan River (Sierra del Rosario, Biosphere Reserve, Cuba) - Larrea-Murrell, Jeny A.; Bacchetti-De-Gregoris, Tristano; Heydrich-Pérez, Mayra; Lugo-Moya, Daysi; Estéve-Núñez, Abraham; Boltes-EspÃnola, Karina; Rojas-Badía, Marcia M. (Tecnología y ciencias del agua, 2021)
The objective of the present study was to analyze the influence of different physicochemical and microbiological indicators on bacterial assemblages in a freshwater ecosystem located in a Biosphere Reserve. The bacterioplankton communities composition was determined by denaturing gradient gel electrophoresis (DGGE) of 16S rDNA during three sampling campaigns in three sampling stations of San Juan River. Multivariate statistical analyses of gel patterns, in relation to chemical, biological and physical parameters were performed. The analyses showed a seasonal variation of bacterial community at the less polluted stations. The correspondence canonical analysis showed that total dissolved solids (TDS), E. coli concentration and dissolved oxygen were significantly influencing the DGGE profiles at San Juan River, indicating that at least two of the three sampling stations analyzed possessed good water quality. With the combination of environmental variables and the DGGE molecular data it could be appreciated the influence of chemical and microbial contamination on the bacterial community of San Juan River. At the less polluted stations low concentrations of TDS and bacterial indicators of fecal contamination were related with bacterial diversity. The present investigation constitutes the first culture-independent analysis of freshwater bacterial communities in a Biosphere Reserve of the Caribbean islands.